Crop Biotechnology and the Future of Food: A Scientific Assessment - Chassy, Bruce M.; Parrott, Wayne A.; Roush, Richard (Council for Agricultural Science and Technology (CAST), 2006)
This CAST Commentary provides an up-to-date evaluation of the use of biotechnology in crop production. The concise, fact-based document addresses the science behind the issues.
Keywords: Biotechnology; Future of Food; Crop Production